MAKNA UGATAMEE SEBAGAI “YANG IMANEN” DALAM KEPERCAYAAN TRADISIONAL SUKU MEE PANIAI-PAPUA - Aris Yeimo; Donatus Sermada Kelen (Pascasarjana Universitas Hindu Indonesia, 2024)
The focus of this article is on the concept of God (Ugatamee) in the traditional faith of the Mee tribe in Paniai - Papua in and through the prayer traditions that have been passed down from generation to generation by their ancestors. They believe that Ugatamee is always present